National Corrections Reporting Program, 1999: (United States) ([Verlag nicht ermittelbar], 2002)
The purpose of this study was to gather data on prisoners entering and leaving the custody or supervision of state and federal authorities. Data refer to prisoners who were admitted to prison (Part 1), released from prison (Part 2), or released from parole (Part 3) in 1999. Variables include incarceration history, current offenses, and total time served. Background information on individuals includes year of birth, sex, age, race, Hispanic origin, and educational attainment.